Synthetic designs regulating cellular transitions: Fine-tuning of switches and oscillators. Issue 25 (March 2021) - Zorzan, Irene; López, Alejandra Rojas; Malyshava, Anastasiya; Ellis, Tom; Barberis, Matteo
Abstract: Biological circuits are responsible for transitions between cellular states in a timely fashion. For example, stem cells switch from an undifferentiated (unstable) state to a differentiated (stable) state. Conversely, cell cycle and circadian clocks are completed through transitions among successive (stable) states, i.e. waves, with (unstable) states switching them at definite timing. These transitions irreversibly determine the biological response or fate of a cell, to commit to reversible switches or to generate periodic oscillations of its state. Here, we review synthetic circuits that, in silico and in vivo, allow a cell to 'make a decision', i.e. to select which state to reach, among multiple ones available, through definite network designs. Specifically, we propose and discuss the designs, and their constituents motifs, which we consider to be more prone to reprogram cell behaviour, and whose parameters can be fine-tuned through systems biology and tested experimentally through Synthetic Biology. For these designs, exploration of the parameter space and of the influence of (external) cellular signals – which modulate circuit parameters – allows for the prediction of the circuit's response and its consequent impact on cell fate. Highlights: Network designs that underlie cellular switches and oscillations are reviewed. Network motifs forming these designs are presented. Tools to investigate occurrence of switches and oscillations are reviewed. Computational and experimental analyses to investigate network designs are presented. Perspectives on reprogramming cellular transitions are discussed.